The World We Want to Live In Compendium of Digitalisation, Digital Networks, and Artificial Intelligence - Schmiedchen, Frank; Kratzer, Klaus Peter; Link, Jasmin S. A.; Stapf-Finé, Heinz (Logos Verlag Berlin, 2022)
Digitalisation, digital networks, and artificial intelligence are fundamentally changing our lives! We must understand the various developments and assess how they interact and how they affect our regular, analogue lives. What are the consequences of such changes for me personally and for our society? Digital networks and artificial intelligence are seminal innovations that are going to permeate all areas of society and trigger a comprehensive, disruptive structural change that will evoke numerous new advances in research and development in the coming years. Even though there are numerous books on this subject matter, most of them cover only specific aspects of the profound and multifaceted effects of the digital transformation. An overarching assessment is missing. In 2016, the Federation of German Scientists (VDW) has founded a study group to assess the technological impacts of digitalisation holistically. Now we present this compendium to you. We address the interrelations and feedbacks of digital innovation on policy, law, economics, science, and society from various scientific perspectives. Please consider this book as an invitation to contemplate with other people and with us, what kind of world we want to live in!